International Study Group of Pancreatic Surgery definitions for postpancreatectomy complications: applicability at a high-volume center - Dusch, Niloufar; Lietzmann, Anja; Rückert, Felix; Wilhelm, Torsten (Scandinavian journal of surgery, 2017)
Introduction:The perioperative morbidity following pancreas surgery remains high due to various specific complications: postoperative pancreatic fistula, postpancreatectomy hemorrhage, and delayed gastric emptying. The International Study Group of Pancreatic Surgery has defined these complications. The aim of this study is to evaluate the clinical applicability, to validate the International Study Group of Pancreatic Surgery definition, and to evaluate the postoperative morbidity.Methods:Between 2004 and 2014, 769 patients underwent resection. Data were collected in a prospective database. Univariate examination was performed using the ?2-test. Continuous data were tested with the Mann?Whitney U-test. Student?s t-tests and Fisher?s exact tests were performed.Results:A total of 542 patients were included in this study. In all, 91 (16.8%) patients developed postoperative pancreatic fistula, 69 of them clinically relevant grades B and C postoperative pancreatic fistula. Grades B and C postoperative pancreatic fistulas were significantly associated with a longer hospital stay. The postoperative pancreatic fistula grade significantly correlated with re-operation. Totally, 32 (5.9%) patients developed postpancreatectomy hemorrhage. Postpancreatectomy hemorrhage grade was significantly associated with re-operation and 30-day mortality. In all, 14 of 19 patients with grade C postpancreatectomy hemorrhage (73.7%) were re-operated; 3 had a simultaneous postoperative pancreatic fistula C. Grade B postpancreatectomy hemorrhage significantly prolonged hospital stay. Grade C postpancreatectomy hemorrhage significantly prolonged intensive care unit stay. Grade C postpancreatectomy hemorrhage led to longer intensive care unit stay but a shorter hospital stay. Delayed gastric emptying occurred in 131 (24.2%) patients. The delayed gastric emptying grade was significantly associated with re-operation. Nine of the re-operated patients had a simultaneous postoperative pancreatic fistula C. Grades A, B, and C delayed gastric emptying were associated with prolonged hospital- and intensive care unit stay.Conclusion:Delayed gastric emptying is the most common specific complication after pancreas resection, followed by postoperative pancreatic fistula and postpancreatectomy hemorrhage. The International Study Group of Pancreatic Surgery definitions are well applicable in clinical routine and the different grades correlate well with severity of clinical condition, length of hospital or intensive care unit stay, and mortality. Their widespread use can contribute to a more reproducible and reliable comparison of surgical outcomes in pancreas surgery.